2007
DOI: 10.1097/bpb.0b013e3280925670
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of postoperative general quality of life for patients with osteosarcoma around the knee joint

Abstract: We evaluated the medium and long-term outcomes on the basis of patients' function and general quality of life after three different surgical procedures for osteosarcoma around the knee joints, that is, amputation, prosthetic reconstruction and rotationplasty. Twenty-six procedures in 22 patients who survived for at least 1 year after surgery were assessed for functional analysis (scores of the Musculoskeletal Tumor Society), and health-related quality of life assessment (SF-36) was applied to 17 patients who a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 20 publications
4
49
1
Order By: Relevance
“…To date, studies have also been conducted to compare the degree of quality of life between patients undergoing limb salvage surgery or amputation. Many of these studies have shown that there is no significant difference in the longterm quality of life between the two groups [15][16][17][18]20]. In contrast to these reports, our results showed that the degree of long term quality of life was higher in the limb salvage surgery group compared with the amputation group.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…To date, studies have also been conducted to compare the degree of quality of life between patients undergoing limb salvage surgery or amputation. Many of these studies have shown that there is no significant difference in the longterm quality of life between the two groups [15][16][17][18]20]. In contrast to these reports, our results showed that the degree of long term quality of life was higher in the limb salvage surgery group compared with the amputation group.…”
Section: Discussioncontrasting
confidence: 56%
“…On the other hand, orthopedic surgeons confront challenging problems related to limb-salvage surgery such as complications associated with the delayed chemotherapy (secondary malignancy or infertility) and postoperative complications such as infection and the mechanical failure or instability of the metal prosthesis [7][8][9]. Many studies have reported on the functional status of the extremities on the affected side in long-term survivors from osteosarcoma [10][11][12][13], however, there are insufficient about the quality of life [14][15][16][17][18][19][20]. So we conducted this study to evaluate the quality of life in longterm survivors from osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…4). However, published reports suggest patients are well adjusted (in terms of SF-36 mental health scores) to the final outcome [1,16]. One concern more recently has been the long postoperative hospital stay compared with amputation.…”
Section: Discussionmentioning
confidence: 99%
“…[62][63] Patients with rotationplasty are reported to have less pain and are more likely to participate in sports as compared to megaprostheses. 61 Akahane et al 64 in a small group of 17 patients reported better function and quality of life results with a rotationplasty than with an endoprosthesis. Rotationplasty is a low cost alternative to prosthesis in a developing country like India.…”
Section: Rotationplastymentioning
confidence: 99%